Identifying Priority Conservation Areas of Largehead Hairtail (Trichiurus japonicus) Nursery Grounds in the East China Sea - Liu, Zunlei; Jin, Yan; Yan, Liping; Zhang, Yi; Zhang, Hui; Shen, Chuyi; Yang, Linlin; Cheng, Jiahua (Frontiers in Marine Science, 2022)
Identifying the spatio-temporal distribution hotspots of fishes and allocating priority conservation areas could facilitate the spatial planning and efficient management. As a flagship commercial fishery species, Largehead hairtail (Trichiurus japonicus) have been over-exploited. Therefore, the spatio-temporal management of hairtail nursing grounds could prove effective for its recovery. This study aims to predict juvenile hairtail distribution patterns and identify priority conservation areas for nursery grounds. A two-stage hierarchical Bayesian spatio-temporal model was applied on independent fishing survey data and geographic/physical variables to analyze the probability of occurrence and abundance distribution of hairtail juveniles. We assessed the importance of each variable for explaining the occurrence and abundance. Using persistence index, we measured the robustness of hotspots and identified persistent hotspots for priority conservation areas. Selected models showed good predictive capacity on occurrence probability and abundance distribution of juvenile hairtail. Dissolved oxygen, net primary production, and sea bottom temperature significantly affected the probability of occurrence, while distance to the coast also affected the abundance distribution. Three stable nursery grounds were identified in Zhejiang inshore waters, the largest one was located on the east margin of the ECS hairtail national aquatic germplasm resources conservation zones (TCZ), suggesting that the core area of nursery grounds occur outside the protected areas. Therefore, recognition of these sites and their associated geographic/oceanic attributes provides clear targets for optimizing hairtail conservation efforts in East China Sea, the eastern and southern areas of TCZ should be included in conservation planning for an effective management within a network of marine protected areas.